2008
DOI: 10.1593/tlo.07100
|View full text |Cite
|
Sign up to set email alerts
|

Combined Resveratrol, Quercetin, and Catechin Treatment Reduces Breast Tumor Growth in a Nude Mouse Model

Abstract: Grape polyphenols can act as antioxidants, antiangiogenics, and selective estrogen receptor (ER) modifiers and are therefore especially relevant for gynecological cancers such as breast cancer. The major polyphenols of red wine (resveratrol, quercetin, and catechin) have been individually shown to have anticancer properties. However, their combinatorial effect on metastatic breast cancers has not been investigated in vivo. We tested the effect of low dietary concentrations of resveratrol, quercetin, and catech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
98
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(108 citation statements)
references
References 44 publications
7
98
2
1
Order By: Relevance
“…Epicatechin acted inhibiting the binding of NF-κB to DNA and inhibited cellular growth on Hodgkin's lymphoma, this inhibition was not associated with epicatechin antioxidant activity (25). Epicatechin was found to have cytotoxic activity, and cells treated with this compound had fragmented nuclei, fragmented DNA, and underwent apoptosis on SW480 human colon cancer (26). Saha et al reported that the combination of curcumin with epicatechin significantly increased the inhibition of cell growth compared with curcumin or epicatechin alone.…”
Section: Discussionmentioning
confidence: 99%
“…Epicatechin acted inhibiting the binding of NF-κB to DNA and inhibited cellular growth on Hodgkin's lymphoma, this inhibition was not associated with epicatechin antioxidant activity (25). Epicatechin was found to have cytotoxic activity, and cells treated with this compound had fragmented nuclei, fragmented DNA, and underwent apoptosis on SW480 human colon cancer (26). Saha et al reported that the combination of curcumin with epicatechin significantly increased the inhibition of cell growth compared with curcumin or epicatechin alone.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, these compounds have been demonstrated to exhibited antioxidant activity [10], the trapping of ultimate carcinogens or the induction of cell apoptosis [11], the inhibition of cell proliferation-related activities [12], the cell cycle arrest [13], the nuclear oncogene expression [14], the inhibition of DNA synthesis [15], and the modulation of signal-transduction pathways by the altered expression of key enzymes such as cyclooxygenases and protein kinases [4]. These effects can be result in altered cell viability through compatibility or cytotoxicity pathways, and thus can be assessed using cell viability assays, such as the BrdU assay [16], clonogenic assay [17], propidium iodide staining [18], trypan blue exclusion [19] or MTT assay [20].…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, using in situ image analysis, we determined that combined dietary polyphenols at 0.5, 5, or 25 mg/kg reduced primary tumor growth of breast cancer xenografts in a nude mouse model. 44 In another study, 34 female patients with histologically confirmed breast cancer, stages IIIB and IV were enrolled in a randomized controlled trial. The Physical Well-Being subscale score of the QOL FACT-B version 4 questionnaire showed a significant difference between the two groups.…”
Section: In Vitro Studiesmentioning
confidence: 99%